Bibliometric and visual analysis of global crc circular RNA research 2015-2023 - Bin, Jian Feng; Chen, Long Fei; Wang, Yan; Ge, Hua; Chen, Wei (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is the third highest malignant tumor in the world in terms of incidence rate, accounting for about 10% of all cancer cases and the second leading cause of cancer related deaths. Timely diagnosis and effective treatment are key to significantly improving the survival rate of CRC patients. Various factors including gender, environmental factors, lifestyle choices, and genetic predisposition are all causes of the onset of CRC. Circular RNA(circRNA) mainly exists in cancer cells and tissues, solid tumors, peripheral blood, exosomes, and body fluids (such as serum, plasma, and saliva). Due to their resistance to degradation and presence in body fluids, CircRNA is non-invasive and an ideal candidate for liquid biopsy, thus having high diagnostic potential. Current research has found that circRNA can regulate the proliferation, migration, invasion, and apoptosis of CRC cells.MethodsThis article aims to comprehensively evaluate the current status and trends of circRNA research in the field of CRC through bibliometric analysis. Intended to use software tools such as VOSviewer, CiteSpace, Microsoft Excel, and R language package to illustrate research progress and focus, in order to outline development trends and future research directions.ResultsThis study used specific inclusion and exclusion criteria to investigate 1048 papers published before December 31, 2023 in the core database of the World Council for Scientific Knowledge. Our research findings indicate that China has the highest number of published papers in this field, with Nanjing Medical University and Kiavash Hushmandi considered the most influential institutions and authors. The Journal ofOncology Frontiers is the journal with the most published papers, while the article "Circular RNA: The New Star of Non coding RNA" is the journal with the most published papers. In addition, terms such as "signaling pathway", "promoting metastasis", "promoting proliferation", and "drug resistance" have become important focuses in this research field.ConclusionsThis study indicates that the focus between circRNA and CRC has shifted from studying the biological characteristics of circRNA to studying the regulation of circRNA molecular mechanisms. Future research should emphasize the potential use of circRNA as a biomarker for the diagnosis, prognosis, and treatment of CRC.